Collaborative Governance on Natural Disaster Management A Study on Forest and Land Fires in Central Kalimantan - Dody Ruswandi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
Forest and land fires repeatedly occur each year in Indonesia, with a variety of sources that bring them about. There are 6 (six) provinces in Indonesia that have always experienced forest and land fires, because these six provinces have the largest peatland in comparison to other provinces. The Central Kalimantan Province experienced the largest forest and land fires in 2015 and 2019. Forest and land fires management involves multi-stakeholders both from the national and regional level. The research was conducted in Pulang Pisau Regency, to examine the collaborative collaboration process between stakeholders that have not functioned optimally. This is why forest and land fires keep on reoccurring annually. The authors conducted an analysis of several existing collaborative governance theories and based on the results of the subsequent analysis the authors recommended a collaboration governance model that is suitable to be applied to fire management on land specifically in Central Kalimantan and Indonesia in general. Here, the author reconstructs the collaborative governance theory of Ansell & Gash (2007) by adding a wisdom variable to become a new variable in implementing collaborative governance in forest and land fire disaste management in Central Kalimantan.